Dietary Correlates of Primate Masticatory Muscle Fiber Architecture. Issue 2 (13th January 2018) - Hartstone‐Rose, Adam; Deutsch, Ashley R.; Leischner, Carissa L.; Pastor, Francisco
ABSTRACT: Analyses of masticatory muscle architecture—specifically fascicle length (FL; a correlate of muscle stretch and contraction speed) and physiological cross‐sectional area (PCSA; a correlate of force)—reveal soft‐tissue dietary adaptations. For instance, consumers of large, soft foods are expected to have relatively long FL, while consumers of obdurate foods are expected to have relatively high PCSA. Unfortunately, only a few studies have analyzed these variables across large primate samples—an order of particular interest because it is our own. Previous studies found that, in strepsirrhines, force variables (PCSA and muscle masses; MM) scale with isometry or slight positive allometry, while the body size corrected FL residuals correlate with food sizes. However, a study of platyrrhines using different methods (in which the authors physically cut muscles between fascicles) found very different trends: negative allometry for both the stretch and force variables. Here, we apply the methods used in the strepsirrhine study (chemical dissection of fascicles to ensure full length measurements) to reevaluate these trends in platyrrhines and extend this research to include catarrhines. Our results conform to the previous strepsirrhine trends: there is no evidence of negative allometry in platyrrhines. Rather, in primates broadly and catarrhines specifically, MM and PCSA scale with isometry or positive allometry. When examining size‐adjusted variables, it is clear that fascicle lengths (especially those of the temporalis muscle) correlate with diet: species that consume soft, larger, foods have longer masticatory fiber lengths which would allow them to open their jaws to wider gape angles. Anat Rec, 301:311–324, 2018. © 2018 Wiley Periodicals, Inc.